The promise of humanistic policing: Is higher education living up to societal expectation? - Carlan, Philip E. (American journal of criminal justice, 2000)
More police agencies require incoming personnel to have a college education background. The hope is that collegeeducated officers will be more rounded thinkers and exhibit a greater humanistic bent. This study attempts to evaluate the efficacy of that line of reasoning. Students from three southern colleges read vignettes and sentenced a murder defendant and an automobile theft defendant to a term of imprisonment. Three hypotheses are tested. First, it is expected that policeoriented criminal justice majors will not issue more severe sentences. Second, it is anticipated that greater exposure to college from the freshman to the senior years will be accompanied by less severe sentences. Third, sentencing will be independent of social characteristics. The results provide little evidence supporting a more authoritarian and more punitive stereotype of criminal justice majors interested in pursuing police careers.